1974
DOI: 10.1093/oxfordjournals.aje.a112036
|View full text |Cite
|
Sign up to set email alerts
|

An “Outbreak” of Juvenile Diabetes Mellitus: Consideration of a Viral Etiology

Abstract: Nine of twelve cases of juvenile diabetes mellitus, representing an unusual geographic and temporal cluster, were investigated for evidence that a specific viral infection might be etiologically related to their occurrence. Eight diabetics had experienced recent "viral-like" illnesses, predominantly repiratory, but these illnesses bore no uniform temporal relation to their onsets of diabetes. Diabetics demonstrated no serologic evidence of a recent viral illness common to all. Elevated titers to only one virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
1

Year Published

1977
1977
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 30 publications
0
16
1
Order By: Relevance
“…Human enterovirus (HEV) infections have long been suspected as environmental triggers of human T1D (12,22,27); infections by common HEVs, such as the group B coxsackieviruses (CVB 1 to 6) and diverse echoviruses, have been implicated as triggers of T1D onset at the time of or shortly after infection (8,9,13,19,28,37,39,40,42,52,60). Nonetheless, it remains unclear whether HEV initiates T1D in humans (18,21,24,26); evidence supporting an etiologic connection between HEV infection and T1D onset is not as well-established as the links between, for example, specific HEV infections and poliomyelitis, aseptic meningitis, or myocarditis (43).…”
mentioning
confidence: 99%
“…Human enterovirus (HEV) infections have long been suspected as environmental triggers of human T1D (12,22,27); infections by common HEVs, such as the group B coxsackieviruses (CVB 1 to 6) and diverse echoviruses, have been implicated as triggers of T1D onset at the time of or shortly after infection (8,9,13,19,28,37,39,40,42,52,60). Nonetheless, it remains unclear whether HEV initiates T1D in humans (18,21,24,26); evidence supporting an etiologic connection between HEV infection and T1D onset is not as well-established as the links between, for example, specific HEV infections and poliomyelitis, aseptic meningitis, or myocarditis (43).…”
mentioning
confidence: 99%
“…Evidence for the contribution of Coxsackievirus B infections in the pathogenesis of type 1 diabetes abounds [13][14][15], yet several other EVs species, including Coxsackievirus A [16][17][18], echoviruses [16,17] and EVs of A-D species [19], may also have a role. Cases of new-onset type 1 diabetes occur in seasonal patterns [11,20], sometimes in clusters or small outbreaks, often peaking 1-2 months after high EV infection activity [21]. A recent study on intrafamilial spread of EV infections reported that 20% of siblings of diabetic probands acquired type 1 diabetes with a latency of 3-25 months [19].…”
Section: Introductionmentioning
confidence: 99%
“…The CVB have been soundly implicated as causes of human myocarditis (1, 26, 42, 60-62, 73, 74, 108, 109) and pancreatitis (2,41,54,58,66,107) and, furthermore, cause these diseases readily in mice (9,40,43,85,86,105). Although CVB have been suggested as infectious triggers of human insulin-dependent (type 1) diabetes mellitus (T1D) (7,22,34,53,116), there is no consensus as to the etiologic role for CVB in T1D development (25,32,33,47,52,63,64,110). Unlike the readiness with which CVB cause pancreatitis and myocarditis in mice, very few CVB strains have been characterized that induce even transient glucose abnormalities or diabetes in inbred strains of mice (56,87,99).…”
mentioning
confidence: 99%